2014
DOI: 10.1212/wnl.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin quantification

Abstract: Objective:We formed a multi-institution collaboration in order to compare dystrophin quantification methods, reach a consensus on the most reliable method, and report its biological significance in the context of clinical trials.Methods:Five laboratories with expertise in dystrophin quantification performed a data-driven comparative analysis of a single reference set of normal and dystrophinopathy muscle biopsies using quantitative immunohistochemistry and Western blotting. We developed standardized protocols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 34 publications
4
85
0
Order By: Relevance
“…Western blot, mass spectrometry, and ELISA excel at quantifying dystrophin in whole tissue samples, but lack fiber-by-fiber data and some techniques are challenged by limits of quantification (i.e. LLOQ of 3–5% for mass spectrometry is too high for DMD patients) (Anthony et al , 2014, Brown et al , 2012). While RT-qPCR does not measure dystrophin levels, this method can be used to measure dystrophin mRNA levels in patients treated with exon-skipping drugs (Anthony et al , 2012).…”
Section: Evaluating Efficacy Of Therapeutic Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot, mass spectrometry, and ELISA excel at quantifying dystrophin in whole tissue samples, but lack fiber-by-fiber data and some techniques are challenged by limits of quantification (i.e. LLOQ of 3–5% for mass spectrometry is too high for DMD patients) (Anthony et al , 2014, Brown et al , 2012). While RT-qPCR does not measure dystrophin levels, this method can be used to measure dystrophin mRNA levels in patients treated with exon-skipping drugs (Anthony et al , 2012).…”
Section: Evaluating Efficacy Of Therapeutic Candidatesmentioning
confidence: 99%
“…Structurally, utrophin shares 80% sequence homology with dystrophin (Schofield et al , 1993, Tinsley et al , 1992). Despite functional differences where dystrophin, but not utrophin, plays a role in microtubule organization and nNOS localization to the sarcolemma, several studies have shown that utrophin improves function in dystrophic muscle (Anthony et al , 2014, Belanto et al , 2014, Janghra et al , 2016, Krag et al , 2004, Rafael et al , 1998, Squire et al , 2002, Tinsley et al , 1992). …”
Section: Introductionmentioning
confidence: 99%
“…Two parallel drug development pipelines are currently investigating the clinical application of exon skipping AOs in DMD. Despite robust discussion, consensus on clinical and functional end points has not been reached, notwithstanding compelling clinical trial data [56] as well as sound and considered evaluation of dystrophin analysis protocols [99]. The ongoing clinical studies are evaluating two different chemistries, 2 0 -OMe AO and PMO, and different oligomer sequences for various exons and use different treatment regimens.…”
Section: Ao Chemistries and Enhanced Deliverymentioning
confidence: 99%
“…A multi-institution collaboration between industry and academia undertook a comparison of dystrophin in patient muscle biopsies, analyzed by western blotting and immunofluorescence [99]. Using standardized protocols, 'Results from the different laboratories were highly concordant with minimal inter-and intra-laboratory variability, particularly with quantitative immunohistochemistry.'…”
Section: Ao Chemistries and Enhanced Deliverymentioning
confidence: 99%
“…Reliable quantification of dystrophin expression in patient biopsy samples remains challenging, and the field has focused on five methods: Western blots, quantitative reverse transcription polymerase chain reaction [RT-qPCR], mass spectrometry, enzyme-linked immunosorbent assay [ELISA]), and immunostaining, (Anthony et al , 2012, Nguyen et al , 1990, Nicholson et al , 1990, Anthony et al , 2014, Brown et al , 2012). To improve further evaluation of immunostaining procedures, several tissue image analysis solutions have been developed to aid in dystrophin quantification (Beekman et al , 2014, Anthony et al , 2014, Taylor et al , 2012).…”
Section: Introductionmentioning
confidence: 99%